Synthesis of Calix[4]resorcinarene Derivatives as Antimalarial Agents through Heme Polymerization Inhibition Assay - Rizky Riyami Putri; Harno Dwi Pranowo; Yehezkiel Steven Kurniawan; Hana Anisa Fatimi; Jumina Jumina (Indonesian Journal of Chemistry, 2023)
Malaria is an endemic disease in tropical countries, including Indonesia, with a high annual mortality rate. Because of that, serious attention shall be given to find new antimalarial agents that are highly active for medical treatment. In this work, we designed and synthesized three calix[4]resorcinarene derivatives and evaluated them as antimalarial agents through in vitro heme polymerization inhibitory assay. The calix[4]resorcinarenes were prepared from resorcinol and corresponding aldehyde derivatives in ethanol media through a cyclo-condensation reaction. The calix[4]resorcinarene products were obtained in 31.1–85.1% yield. The synthesized compounds were subjected to structure elucidation using spectroscopy techniques. The antimalarial activity of calix[4]resorcinarene with aromatic substituent (IC50 = 0.198 mg/mL) was higher than the aliphatic ones (IC50 = 0.282–0.814 mg/mL). It was found that all calix[4]resorcinarenes in this work exhibited stronger antimalarial activity than chloroquine diphosphate as the positive control (IC50 = 1.157 mg/mL). The calix[4]resorcinarenes could interact with hydrogen bonding, thus inhibiting the heme polymerization process. These findings demonstrate that calix[4]resorcinarene derivatives are potential antimalarial agents to be developed for effective medical treatment in the near future.